BRCA1 promoter methylation predicts PARPi response in ovarian cancer: insights from the KOMET study - Léna Nougarede; Florence Hazane-Puch; Florence de Fraipont; Emmanuelle Jacquet; Marie Bidart (Clinical Epigenetics)
Abstract Objectives PARP inhibitors (PARPi) have become the new standard maintenance treatment for patients with advanced homologous recombination deficiency (HRD) ovarian cancer; they are also used upon platinum-sensitive relapse. HRD in ovarian cancer is primarily assessed through BRCA genes mutations and genomic scar scores, which are key biomarkers forecasting PARPi benefit. However, the role of BRCA1 promoter methylation in guiding clinical management is unclear. Evidence is needed to improve patient selection before initiating PARPi and to minimize PARPi-related toxicities. Our study aimed to determine the clinical relevance of BRCA1 promoter methylation for patients with ovarian carcinoma. Method The KOMET (Ovarian Cancer Methylation) study is a single-center retrospective study involving 88 ovarian cancer patients treated between January 2021 and July 2024. Methylation was assessed using Methylation specific high-resolution melting (MS-HRM). Outcomes were measured based on progression-free survival (PFS) from diagnosis and from the initiation of PARPi treatment, as well as overall survival (OS). Results A methylated BRCA1 promoter was detected in 17 out of 88 (19%) tumor tissues. Statistically, PFS from PARPi initiation was significantly different between the BRCA1 methylated promoter (BRCA1mp) group and the BRCA1 unmethylated promoter and HRD negative (BRCA1up HRD−) group (p value = 0.0003 log rank test; Hazard Ratio (HR), 95% CI 0.04–0.40). OS was also significantly different between these groups (p value = 0.047 log rank test; HR = 0.30, 95% CI 0.10–0.84), as was PFS from diagnosis (p value = 0.02 log rank test; HR = 0.43, 95% CI 0.21–0.89). Conclusion BRCA1 promoter methylation in ovarian cancer is associated with a better response to PARPi and platinum salt chemotherapy than tumors without promoter methylation or classical homologous recombination deficiency. Patients with unmethylated BRCA1 promoters and HRD-negative tumors appeared to have a poorer prognosis in terms of PFS from diagnosis. BRCA1 methylation should be considered as a theragnostic biomarker for initiation of PARPi.